Marine algal flora of Pico Island, Azores - Neto, Ana I. (2020)
BACKGROUND: The seaweed flora of Pico Island (central group of the Azores archipelago) has attracted interest of researchers on past occasions. Despite this, the macroalgal flora of the island cannot be considered well-known as published information reflects only occasional collections. To overcome this, a thorough investigation encompassing collections and presence data recording was undertaken. Research under the Campaigns "AÇORES/89", "PICO/91", "PICOBEL/2007" and "LAUMACAT/2011" covered a relatively large area (approximately 39 km2) around the island, encompassing the littoral and sublittoral levels down to about 40 m around the Island.This paper improves the knowledge of the Azorean macroalgal flora at local and regional scales by listing taxonomic records and providing information on the ecology and occurrence of each species present on the Island's littoral. NEW INFORMATION: A total of 4043 specimens (including taxa identified only to genus level) belonging to 303 taxa of macroalgae are registered, comprising 197 Rhodophyta, 53 Chlorophyta and 53 Ochrophyta (Phaeophyceae). From these, 225 were identified to species level (142 Rhodophyta, 41 Chlorophyta and 42 Ochrophyta), encompassing 110 new records for the island (69 Rhodophyta, 20 Chlorophyta and 21 Ochrophyta), three Macaronesian endemisms (Botryocladia macaronesica Afonso-Carillo, Sobrino, Tittley & Neto; Laurencia viridis Gil-Rodríguez & Haroun; Codium elisabethiae O. C. Schmidt), 14 introduced and 25 species with an uncertain status.